2017
DOI: 10.18280/ijht.350309
|View full text |Cite
|
Sign up to set email alerts
|

Double vortex generators for increasing the separation efficiency of the air separator

Abstract: This article presents a numerical analysis of multi-phase flow with powerful swirling streams in a cylindrical separator equipped with two vortex generators in an attempt to predict the separation efficiency of an air-water mixture. New design of a cylindrical separator is introduced for air-water mixture.The mixture multiphase and large eddy simulation (LES) turbulence models were applied. Images that concern velocity field, pressure, and volume fraction are introduced. Air phase is trapped and localized alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is a known fact that high turbulence with swirling flow enhances particles and fluid mixing [4]. Detailed study on swirling flow can be found in [5,6,7,8]. Many attempts have also been made to model the minimum velocity of slurry flow at which solid particles in the flow will remain suspended in the flowing fluid stream (Critical Velocity) and below which the particles start depositing to form sliding bed (Critical deposition velocity).…”
Section: Introductionmentioning
confidence: 99%
“…It is a known fact that high turbulence with swirling flow enhances particles and fluid mixing [4]. Detailed study on swirling flow can be found in [5,6,7,8]. Many attempts have also been made to model the minimum velocity of slurry flow at which solid particles in the flow will remain suspended in the flowing fluid stream (Critical Velocity) and below which the particles start depositing to form sliding bed (Critical deposition velocity).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no guiding rules could be established for predicting the occurrence of counteracting wind and stack effects, since no consistent trends were observed. k-ε turbulent model, Reynolds stress turbulent model and Large eddy simulation turbulent models are also frequently used to incorporate the turbulence effect in flow inside or over a domain [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Swirl flow demonstrates nearly 22% enhancement of Nu and nearly 19% reduction of the T s compared to the axial flow. In addition, utilizing jet vortex technology was found to be very useful in enhancing the separation efficiency of air separators 7 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, utilizing jet vortex technology was found to be very useful in enhancing the separation efficiency of air separators. 7 Rennie et al 8 carried out an experimental study on a helical heat exchanger. Experimental data agreed with numerical data for larger heat exchangers in terms of Nusselt number, but there were some differences between numerical data and experimental data for smaller heat exchangers.…”
Section: Introductionmentioning
confidence: 99%